2019
DOI: 10.1002/esp.4682
|View full text |Cite
|
Sign up to set email alerts
|

Temporal variation in suspended sediment transport: linking sediment sources and hydro‐meteorological drivers

Abstract: Suspended sediment concentrations (SSCs) in rivers are variable in time due to interacting soil erosion and sediment transport processes. While many hydro‐meteorological variables are correlated to SSCs, interpretation of these correlations in terms of driving processes requires in‐depth knowledge of the catchment. Detailed sediment source information is needed to establish the causal linkages between driving processes and variations in SSC. This study innovatively combined sediment fingerprinting with multiva… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
16
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 18 publications
(16 citation statements)
references
References 72 publications
0
16
0
Order By: Relevance
“…Furthermore, during the drying period, more urban street dust could have been built up on the streets and then washed away during the event (Old et al 2003). This hypothesis is supported by findings from a sediment fingerprinting study applied to the SS samples collected during this event, which suggest that urban street dust and eroding grassland from the upper part of the catchment were dominant SS sources during the event (Vercruysse and Grabowski 2019). As the event progressed, component 1 became the dominant factor controlling SSC.…”
Section: High-flow Eventsmentioning
confidence: 57%
See 2 more Smart Citations
“…Furthermore, during the drying period, more urban street dust could have been built up on the streets and then washed away during the event (Old et al 2003). This hypothesis is supported by findings from a sediment fingerprinting study applied to the SS samples collected during this event, which suggest that urban street dust and eroding grassland from the upper part of the catchment were dominant SS sources during the event (Vercruysse and Grabowski 2019). As the event progressed, component 1 became the dominant factor controlling SSC.…”
Section: High-flow Eventsmentioning
confidence: 57%
“…This change can be an indication that soils were increasingly saturated, causing saturation excess overland flow to become the dominant process for erosion and SS transport to and into the river, and is supported by an increase in SS contribution from eroding grassland less connected to the river due to scattered urban areas (Coal Measures area, Fig. 2) (Vercruysse and Grabowski 2019). Similarly, prolonged precipitation in November 2016 (Fig.…”
Section: High-flow Eventsmentioning
confidence: 96%
See 1 more Smart Citation
“…However, few studies delve into the relationship of transport processes with hydro-meteorological drivers, which are especially relevant in mountainous environments (e.g. Micheletti and Lane, 2016;Lane et al, 2017;Kumar et al, 2018;Rainato et al, 2018;Vercruysse and Grabowski, 2019). In these areas, the dynamics of suspended sediment are greatly influenced by the torrential nature of rainfall, snow cycles and high local atmospheric and topographic gradients.…”
Section: Introductionmentioning
confidence: 99%
“…In mesoscale catchments (<100 km²), which correspond to a relevant scale for decision makers, correct modeling of the hydrosedimentary responses requires a good understanding of the interactions between the spatiotemporal dynamics of the rainfall with the spatial distribution of the catchment geomorphological characteristics. Several studies have shown that the contributions of potential sediment sources can differ considerably from one flood event to another and at different times of sampling within a flood event (Brosinsky et al, 2014 ;Gourdin et al, 2014;Cooper et al, 2015;Gellis and Gorman Sanisaca, 2018;Vercruysse and Grabowski, 2019), particularly in Mediterranean and mountainous watersheds (Evrard et al, 2011 ;Navratil et al, 2012;Poulenard et al, 2012;Legout et al, 2013;Uber et al, 2019). Possible reasons for the observed variability of suspended sediment fluxes from one event to another include seasonal variations of the climatic drivers of soil erosion and sediment transport, variability of the spatial distribution of rainfall, land cover changes and human interventions (Vercruysse et al, 2017).…”
mentioning
confidence: 99%